1996
DOI: 10.1073/pnas.93.25.14580
|View full text |Cite
|
Sign up to set email alerts
|

Peptides containing glutamine repeats as substrates for transglutaminase-catalyzed cross-linking: Relevance to diseases of the nervous system

Abstract: Many proteins contain reiterated glutamine residues, but polyglutamine of excessive length may result in human disease by conferring new properties on the protein containing it. One established property of a glutamine residue, depending on the nature of the flanking residues, is its ability to act as an amine acceptor in a transglutaminase-catalyzed reaction and to make a glutamyl-lysine cross-link with a neighboring polypeptide. To learn whether glutamine repeats can act as amine acceptors, we have made pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
132
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 44 publications
5
132
0
Order By: Relevance
“…Interestingly, the A-type repeats display the highest homology to HRNR (8), an epidermal protein recently shown to be a component of cornified cell envelopes (28). A-type repeats of FLG2 and HRNR both contain high percentages of Gln (15 and 9.4%, respectively), which is a key amino acid for transglutaminase-mediated cross-linking to the cornified envelope (53,54), suggesting that the A-type repeat domain is cross-linked to these corneocyte structures.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the A-type repeats display the highest homology to HRNR (8), an epidermal protein recently shown to be a component of cornified cell envelopes (28). A-type repeats of FLG2 and HRNR both contain high percentages of Gln (15 and 9.4%, respectively), which is a key amino acid for transglutaminase-mediated cross-linking to the cornified envelope (53,54), suggesting that the A-type repeat domain is cross-linked to these corneocyte structures.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies of glutamine repeats in synthetic peptides made by solid-phase synthesis showed that increasing the number of consecutive glutamine residues led to increased reactivity of each residue in a transglutaminase-catalyzed reaction; ultimately as many as 80% of the total glutamine residues participated in the reaction (9). Experiments by others showed that the addition of polyQ to the protein GST greatly increased its reactivity as a transglutaminase substrate (10).…”
mentioning
confidence: 85%
“…The devastating Altzheimer's disease might be derived from the crosslinking of the neurofilaments, microtubule-associated tau proteins, or amyloid β proteins (Selkoe et al, 1982;Miller and Anderton, 1986;Lorand, 1996). The gene products with polyglutamine tracts whose length is determined by the number of CAG repeats could be the putative substrates for TGase, associated with Huntington's disease, spinocerebellar ataxia type I, dentarubral-phallidoluysian atrophy, spinobulbar muscular atrophy and spinocerebeller ataxia type 3 (Cariello et al, 1996;Kahlem et al, 1996). The midkine, a highly basic heparin-binding cytokine, dimerized by a TGase can stabilize the growth factor, endowing its neurite-promoting activity amplification (Mahoney et al, 1986).…”
Section: Five Different Types Of Tgases From the Mammalian 181mentioning
confidence: 99%